Household knowledge, attitudes and practices related to pet contact and associated zoonoses in Ontario, Canada - Stull Jason W; Peregrine Andrew S; Sargeant Jan M; Weese J (BMC, 2012)
Abstract Background Many human infections are transmitted through contact with animals (zoonoses), including household pets. Although pet ownership is common in most countries and non-pet owners may have frequent contact with pets, there is limited knowledge of the public's pet contact practices and awareness of zoonotic disease risks from pets. The objective of this study was to characterize the general public's knowledge, attitudes and risks related to pet ownership and animal contact in southern Ontario, Canada. Methods A self-administered questionnaire was distributed to individuals at two multi-physician clinics in Waterloo, Ontario, Canada during 2010. A single adult from each household was invited to participate in the study. Results Seventy five percent (641/853) of individuals approached completed the questionnaire. Pet ownership and contact were common; 64% of participants had a pet in their household and 37% of non-pet owning households had a member with at least weekly animal contact outside the home. Pet ownership was high (55%) for households with individuals at higher risk for infections (i.e., < 5 yrs, ≥ 65 yrs, immunocompromised). Most respondents (64%) indicated that they had never received information regarding pet-associated disease risks. When given a list of 11 infectious pathogens, respondents were only able to correctly classify just over half on their potential to be transmitted from pets to people (mean 6.4); independently, pet owners and those who recalled receiving information in the past about this topic were able to make significantly more correct identifications. Pet (36%) and non-pet owning households (10%) reported dog or cat bites or scratches during the preceding year. Households with individuals at higher risk for an infection did not differ from the remaining households regarding their perceived disease risk of pets, zoonotic disease knowledge, recall of being asked by their medical provider if they owned any pets, or recall of having received information regarding pet-associated disease risks and preventive measures. Conclusions These results suggest that there is a need for accessible zoonotic disease information for both pet and non-owning households, with additional efforts made by veterinary, human and public health personnel. Immediate educational efforts directed toward households with individuals at higher risk to infections are especially needed.